Forming of Professionally-Creative Abilities of Students in the Process Of Creative Dialogue Co-Operation of Subjects of Educational Process - Protsenko, Iryna (Pedagogical Discourse, 2014)
In the article the content of experimental research of heuristic dialogue as to the method of the successful forming of professional abilities of creative character of future teachers of humanitarian disciplines has been revealed: intellectual, structural, организационно-регулятивных and dialogic-heuristic. The basic stages (motivational, process-active and diagnostic) of forming of such abilities, criteria, are distinguished for the diagnostic measuring of their level. The important role of professionally-creative dialogue abilities is found out at forming creative educational products (work-reflection, story, scientific project, report, essay, heuristic conversation) is primary purpose of heuristic educational activity. The features of application of interrogative activity in group organization of studies of students are determined.